LAND OWNING PATTERNS ON RICE FARMING: Increasing Production and Efficiency - Untari Untari; Maria Veronoca Irene Herdjiono (Universitas Lancang Kuning, 2020)
Merauke has a large potential for agricultural land with a type of agriculture that can be developed, namely a wetland farming system that is very suitable for paddy production. The objectives of this study are: a) to know the patterns of paddy farming, b) analyze the level of production from land tenure patterns, and c) analyze the level of economic efficiency of paddy farming in the pattern of paddy farmland ownership in Marga Mulya village, Semangga District, Merauke Regency. The study used 60 respondents as a source of data and information on primary research data. Data analysis method used to answer the research objectives is farming analysis and R/C ratio. The results of the study concluded that there are two patterns of rice farming land ownership, namely the pattern of ownership of private land and leased land. The two patterns of land ownership show that the pattern of ownership of private land has a higher production compared to the pattern of ownership of rent versus 2,785.71 kg/ha/season and 2,313 kg/ha/season with an efficiency level of 2.57% and 2.51%.